2016
DOI: 10.5863/1551-6776-21.6.486
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of and Risk Factors for Acute Kidney Injury Associated With Vancomycin Use in the Pediatric Intensive Care Unit

Abstract: BACKGROUND:Published information evaluating frequency of and risk factors for vancomycin-induced acute kidney injury (AKI) in the pediatric intensive care unit (PICU) population is conflicting. OBJECTIVES: The primary objective was to describe the proportion of our PICU patients who developed AKI with intravenous (IV) vancomycin. The secondary objective was to describe the associated potential risk factors. METHODS: Pediatric patients (0-18 years) who received their first IV vancomycin dose in the PICU were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 11 publications
0
36
1
Order By: Relevance
“…A total of 17 studies reporting PK-parameters of vancomycin in critically ill children were identified by the search, with more than 1000 PICU patients included in total over the whole pediatric age range [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Most studies included a mixed population, but also specific populations (such as patients with hematologic/oncologic [43,45], cardiac [51,53,56,57], traumatic [50] and infectious diseases [44,48]) being studied separately.…”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 17 studies reporting PK-parameters of vancomycin in critically ill children were identified by the search, with more than 1000 PICU patients included in total over the whole pediatric age range [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Most studies included a mixed population, but also specific populations (such as patients with hematologic/oncologic [43,45], cardiac [51,53,56,57], traumatic [50] and infectious diseases [44,48]) being studied separately.…”
Section: Vancomycinmentioning
confidence: 99%
“…Most studies used intermittent dosing with daily doses of vancomycin ranging from 30 to 60 mg/kg/day, with only 1 study reporting higher mean doses (81 mg/kg/day) [45] and 1 study not mentioning the dose at all [41]. Two studies reported data on continuous dosing schedules, using a loading dose of 15 mg/kg and a maintenance dose of 40-45 mg/ kg over 24 h [42,55].…”
Section: Vancomycinmentioning
confidence: 99%
“…pRIFLE defines loss of kidney function as renal failure for at least 4 weeks and end stage renal disease as failure for at least 3 months. 6 Patients were evaluated for any level of kidney dysfunction (risk, injury, or failure) within the first 14 days of therapy or the end of their therapy, whichever occurred first. The primary outcome was defined as the incidence of acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cies and colleagues evaluated beta lactam monotherapy compared to combination therapy with vancomycin and did not find a statistically significant difference in the incidence of renal injury (8.8% vs 8.9%, P = 1) in a critically ill pediatric population, despite a mean vancomycin trough of 17.8 ±3.1 mcg/mL. 6 In a subsequent study completed by the same group, they did not observe a statistically significant difference in the rate of nephrotoxicity (8.8% vs 5.4%, P = 0.72), despite different target vancomycin trough concentrations (17.5 vs 8.4 mcg/mL, P < 0.001). Nephrotoxicity was defined as an increase in SCr > 0.3 mg/dL or 1.5-2 times baseline.…”
Section: Utilization Of Anti-pseudomonal Beta Lactams For Double Covementioning
confidence: 98%
See 1 more Smart Citation